Factors associated with complications and postoperative visual outcomes of cataract surgery; A study of 1,632 cases - Thevi, Thanigasalam; Rafdzah, Ahmad Zaki; Sagili Chandrashekara, Reddy (Wolters Kluwer Medknow Publications, 2015)
Purpose: Cataract surgery is the most common intraocular surgery performed all over the world and has advanced technically in recent years. As in all surgeries, complications are unavoidable. Herein we report factors associated with complications and visual outcomes of cataract surgery.